Sagot :
Answer:
1. 7x
2. 19x
3. 6x
4. 35x
5. -x
6. -3x + 8y
7. 12x +3y
8. x + 9y
9. 4x + 13y
10. 5x + 10y
Step-by-step explanation:
1. 8x + (- 3x) - (-2x) → 8x - 3x +2x = 7x
2. 12x - 4x + 16x - 5x → 8x + 11x = 19x
3. ) (-2x) + (-4x) - (- 5x) + 7x → -2x - 4x + 5x + 7x = 12x - 6x = 6x
4. 3x - 3 (-9x) + 5x → 3x + 27x + 5x = 35x
5. 11x + 3x - 25x + 10x → 14x - 15x = -x
6. 4x + 3y - 7x + 5y → 4x - 7x + 5y + 3y = -3x + 8y
7. 9x + 6y + 3x + (-3y) → 9x + 3x + 6y - 3y = 12x +3y
8. 5y - 6x + 7x + 4y → 7x - 6x +4y + 5y = x + 9y
9. ) (10x - 5y) - (6x - 18y) → 10x - 5y - 6x + 18y = 4x + 13y
10. 9x + 12y - 2y + (-4x) → 9x - 4x + 12y - 2y = 5x + 10y